Perlindungan Hak Kekayaan Intelektual (HKI) Musisi di Industri Musik Indonesia: Studi Yuridis Terhadap Tantangan Penegakan Hak Cipta dan Distribusi Royalti di Era Digital - Mousavian, Farel Sya'ban; Lie, Gunardi (Program Studi Hukum Ekonomi Syariah, Institut Agama Islam Negeri Parepare, 2025)
This study examines the protection of Intellectual Property Rights (IPR) for musicians in Indonesia’s music industry, focusing on the challenges of copyright enforcement and royalty distribution in the digital era. The research employs a normative juridical method with statutory, conceptual, and case approaches, supported by library research. The findings reveal that copyright enforcement faces significant obstacles, including rampant digital piracy, limited law enforcement capacity, weak institutional coordination, and low public awareness of copyright compliance. Meanwhile, royalty distribution mechanisms remain ineffective due to lack of transparency, delayed payments, and the complex flow of digital revenues involving multiple stakeholders. These shortcomings undermine the effectiveness of IPR protection for musicians. Therefore, strategic measures are required, such as strengthening law enforcement capacity, enhancing the transparency and accountability of collective management organizations, and utilizing digital technologies such as fingerprinting, blockchain, and smart contracts. Synergy between law enforcement, royalty distribution governance, and technological innovation is essential to build a fair, transparent, and sustainable music ecosystem in Indonesia. Keywords: Intellectual Property Rights, copyright, royalty distribution, music industry, digital era